Access to the most selective private colleges by high-ability, low-income students: Are they out there? - Gordon C. Winston; Catharine B. Hill (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2005)
With only a small number of their students coming from families with the lowest incomes (10% from the bottom two family income quintiles), the nation's most selective private colleges and universities need to know why. Two ready ideological answers are (1) that low-income high-ability students are being excluded in order to favor the children of society's most advantaged or (2) that very few low-income high-ability students exist - that by college age, low-income students have been so damaged by education, nutrition, neighborhoods, and families that few can qualify in a perfectly fair admissions process. This paper uses the national population of high school test-takers in 2003 to examine the national distribution over family incomes of high-ability students (variously defined). With these data, two questions can be addressed. What would be the target share of low-income students at these schools if their student bodies were to mirror the national high-ability population? And, are they out there - do there exist enough such low-income, high-ability students to meet those targets? It is shown that they are out there - that a somewhat larger share of the test-taking population is made up of high-ability, low-income students than are found in these schools and that their numbers make it feasible for the schools to increase their enrollments to target that national share. Because much depends on the definition of high-ability used, we consider alternative definitions but reach the same conclusion at any reasonable level (like a minimum combined SAT of 1300 or even 1420).
Keywords: 330; Privatuniversität; Studierende; Niedrigeinkommen; Bildungsverhalten; Schätzung; USA